Influences of B4C content and particle size on the mechanical properties of hot pressed TiB2–B4C composites. Issue 3 (3rd July 2021) - Zhao, Jun; Li, Qinggui; Cao, Weixiao; Liu, Zetan; Deng, Xiangong; Ding, Xiang; Ran, Songlin
ABSTRACT: TiB2 ceramic has attracted many attentions due to its excellent performances both on mechanical and functional properties. However, it is still very difficult to obtain TiB2 bulks with full densification. Herein, TiB2 –B4 C composites were prepared via hot pressing at 1900°C under the pressure of 35 MPa with TiB2 and B4 C as the raw materials. The influences of B4 C content (0, 10 vol%, 20 vol% and 30 vol%) and particle size (0.50 µm, 3.12 µm and 7.09 µm) on the phase composition, relative density, microstructure and mechanical properties of TiB2 –B4 C composites were investigated. The using of 0.50 µm B4 C brought more B2 O3 which induced oriented growth of TiB2 grains and coarsened the obtained composites. When the raw B4 C powders were 3.12 µm and 7.09 µm, the obtained composites with 20–30 vol% B4 C could be fully densified. TiB2 –30 vol% B4 C composite prepared from 3.12 µm B4 C powder resulted in the optimal mechanical properties. The bending strength, Vickers hardness, fracture toughness were 671 MPa, 27.93 GPa, and 3.91 MPa·m 1/2, respectively. The excellent performance was attributed to its fine and homogenous microstructure.